Relational governance of territorial resources in post-colonial Africa – A new analytic framework - Rothfuß, Eberhard; Boamah, Festus; Dörfler, Thomas (DIE ERDE – Journal of the Geographical Society of Berlin, 2021)
Current political sociology scholarship suggests that limited state autonomy from societal organisations undermines state enforcement capacity throughout the national territory, and therefore does superficial separation of the state from civil society (or formal from informal institutions) in the conceptualisation of what effective state system ought to be. These conceptions contradict realities in post-colonial Africa where societal organisations have evolved to bear ‘state-like’ qualities in resource governance, especially in remote locations where the state has no promising alternative to accommodating inputs from revered institutions or charismatic actors to complement its functions. Colonial experiences in Africa have produced institutional pluralism and a consequential split loyalty to the state in the post-independence era. Apparently, limited state autonomy sometimes refract or obstruct state visions; the resultant co-governance regime does not imply ‘wishy-washy’ state leadership. This is because state formation processes have produced an intermeshed governance of people, places, and resources through a complicated interplay between entities which have become indistinct in terms of functions, and hence cannot be simplistically categorised as either formal or informal, state or non-state. In this sense, the activity of regulating affairs in the post-colonial regime is characterised by relational governance – a form of governance sutured via reciprocal relation(s) between multiple actors across different spatial scales and milieus. Drawing on an empirical study of biofuel projects in Ghana, we believe a relational governance approach provides an analytic framework to challenge this orthodoxy in governance studies and refresh discussions on the nature of state-society relations required for effective governance of territorial resources in postcolonial regimes characterised by institutional pluralism.